2017
DOI: 10.3329/ajmbr.v3i3.34528
|View full text |Cite
|
Sign up to set email alerts
|

Economics of fish production in paddy fields in Bangladesh

Abstract: This study was conducted to assess profitability of fish production in paddy fields in the village of Kunia and Chandora, under Gacha union in Gazipur sadar upazila in Gazipur district. Primary data were collected from 15 fish farmers for the study during the period from June to November, 2016. Production performance of three stocking package were compared. CFP-1 package contained Thai sarpunti (24700/ha) + Tilapia (6175/ha); CFP-2 comprised of Thai sarpunti (24700/ha) + Common carp (6175/ha); while CFP-3 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
5
9
2
Order By: Relevance
“…Revenue that is gained from mud crab treated with snail and tilapia did not varied significantly. The present study showed that chicken intestine could be alternative inexpensive feed for mud crab with higher growth and economic performance and it was comparable to Chilok and Hanafi (1992) and Rahman et al (2017). Rabia (2016) reported that Mud crab fed with golden apple snail constitute the high return of investment compared to the other treatments as indicated that low expenses incurred during the conduct of the study because feeds are readily available and this statement was similar for the current experiment where chicken intestine provided highest return .…”
Section: Discussionsupporting
confidence: 83%
“…Revenue that is gained from mud crab treated with snail and tilapia did not varied significantly. The present study showed that chicken intestine could be alternative inexpensive feed for mud crab with higher growth and economic performance and it was comparable to Chilok and Hanafi (1992) and Rahman et al (2017). Rabia (2016) reported that Mud crab fed with golden apple snail constitute the high return of investment compared to the other treatments as indicated that low expenses incurred during the conduct of the study because feeds are readily available and this statement was similar for the current experiment where chicken intestine provided highest return .…”
Section: Discussionsupporting
confidence: 83%
“…These results indicate that the use of drugs, providing adequate condition and the use of healthy and good quality with the proper size of fingerlings might directly increase the income. This statement is also true for using good quality and healthy feed in fish farming (Kitessa et al, 2014;Phu et al, 2015;Rahman et al, 2017). For example, a Cobb-Douglas production function analysis by Rahman et al (2017) showed that fish fingerlings and fish feeds were positively contributed to the total income as well as farm productivity.…”
Section: Production Functionmentioning
confidence: 99%
“…This statement is also true for using good quality and healthy feed in fish farming (Kitessa et al, 2014;Phu et al, 2015;Rahman et al, 2017). For example, a Cobb-Douglas production function analysis by Rahman et al (2017) showed that fish fingerlings and fish feeds were positively contributed to the total income as well as farm productivity. The observations of the present study are also agreed with the previous studies by Kareem et al (2008), Agboola (2011), Aydin et al(2014 and Tunde et al (2015), they showed the positive effect of those variables on the gross profit.…”
Section: Production Functionmentioning
confidence: 99%
“…The present findings are somewhat lower than the findings were obtained from Samad et al (2014) who studied that the CBR was highest in T 3 (1:1.24) and the lowest was found in T 1 (1:0.056) for Clarias batractus in ponds. Similar economics were assessed by Rahman et al (2017) elsewhere in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%